TRANSAKSI AKAD MUDHARABAH PADA PEMBIAYAAN USAHA DALAM PESANTREN DI PROVINSI RIAU MENURUT PERSFEKTIF MAQASHID SYARIAH - Yuni Armayanti; Lailatul Husna; Sugito Sugito (KASBANA, 2026)
Abstract This study analyzes the implementation of Islamic economic law in the Islamic boarding school (pesantrenpreneur) model in Riau Province, focusing on the suitability of sharia contracts and their contribution to the economic empowerment of the community. The research method used is normative law combined with a qualitative case study approach in three Islamic boarding schools (pesantren) in Pekanbaru, Kampar, and Rokan Hilir. Data were collected through in-depth interviews, participant observation, and documentation studies, analyzed using the interactive model of Miles and Huberman. The results show that Islamic boarding school (pesantrenpreneur) has established a sharia economic ecosystem that integrates da'wah values with business practices, using mudharabah, musyarakah, and productive waqf contracts. However, the findings reveal substantive deficiencies in the contract documents, particularly the absence of explicit clauses regarding loss settlement mechanisms and risk distribution, as well as weaknesses in sharia supervision of productive waqf. From the perspective of maqashid sharia, although the principle of halalan thayyiban has been implemented, there are gaps in the accountability of fund management (hifzh al-mal) and consumer protection (hifzh al-nafs). This study recommends institutional restructuring, refinement of contract documents, and strengthening of the sharia supervisory system to ensure comprehensive compliance with sharia economic principles. Keywords: Islamic Boarding School Entrepreneur, Sharia Economic Law, Sharia Contracts, Maqasid Sharia, Economic Empowerment